2021
DOI: 10.1002/1878-0261.12930
|View full text |Cite
|
Sign up to set email alerts
|

EWI‐2 controls nucleocytoplasmic shuttling of EGFR signaling molecules and miRNA sorting in exosomes to inhibit prostate cancer cell metastasis

Abstract: Early and accurate diagnosis of prostate cancer (PCa) is extremely important, as metastatic PCa remains hard to treat. EWI-2, a member of the Ig protein subfamily, is known to inhibit PCa cell migration. In this study, we found that EWI-2 localized on both the cell membrane and exosomes regulates the distribution of miR-3934-5p between cells and exosomes. Interestingly, we observed that EWI-2 is localized not only on the plasma membrane but also on the nuclear envelope (nuclear membrane), where it regulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Studies have shown that specific miRNAs delivered by exosomes can affect the function of cocultured cells ( 19 , 37 ). These results indicate that miRNAs in plasma exosomes can be transported to recipient cells through exosomes and then regulate functions of cells, although the parental cells of plasma exosomes selected in this study are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that specific miRNAs delivered by exosomes can affect the function of cocultured cells ( 19 , 37 ). These results indicate that miRNAs in plasma exosomes can be transported to recipient cells through exosomes and then regulate functions of cells, although the parental cells of plasma exosomes selected in this study are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…According to the role of exosomes in influencing cancer progression, a significant attempt has been made to reveal the role of exosomes in clinical background [504][505][506][507][508]. The genes contained in exosomes can be considered as biomarkers for the diagnosis of lung cancer.…”
Section: Clinical Application and Role Of Exosomes As Biomarkersmentioning
confidence: 99%
“…In addition to RBPs, other proteins or lipids have been reported to participate in miRNA sorting. Most recently, EWI-2 was found to be enriched in EVs and regulate the sorting of multiple miRNAs into EVs [ 32 ]. EWI-2 is a member of the Ig protein subfamily that functions as a TGFβ signal inhibitor and regulates cancer cell proliferation and metastasis [ 33 ].…”
Section: Noncoding Rna Sorting Into Evsmentioning
confidence: 99%
“…EWI-2 is a member of the Ig protein subfamily that functions as a TGFβ signal inhibitor and regulates cancer cell proliferation and metastasis [ 33 ]. EWI-2 is localized on both plasma membranes and the nuclear envelope, and the EWI-2 knockout enforces miR-3934–5p packaging into sEVs and targets EGFR signaling [ 32 ]. Interestingly, the cytoplasmic tail of EWI-2 actively engages with the cell membrane via phosphatidylinositol phosphate (PIP) binding and palmitoylation [ 34 ], suggesting that membrane lipids could mediate RNA sorting.…”
Section: Noncoding Rna Sorting Into Evsmentioning
confidence: 99%